O impacto do covid-19 na atividade física dos professores da rede pública e privada de Belém do Pará - PAIVA FILHO, Paulo Cézar Colorado Damasceno de (2023)
As a result of the Covid-19 pandemic, various spheres of society were affected in an unforeseen way. In order to prevent the spread of the virus, regulations were adopted in all countries, including social distancing and quarantine, which resulted in the suspension of face-to-face activities in all Brazilian public and private educational institutions. In view of this reality, the present thesis aims to investigate the impact of Covid-19 on the physical activity of teachers at educational institutions in Pará, based on a questionnaire with closed questions, analyzing their practices before and during the pandemic period. From the data collected with the questionnaire, we listed the questions that were directly related to the physical activity of the teachers, and a significant reduction in the activities usually performed by the sample of 154 participants was measured. The results of the present study showed that, as in other countries, the daily physical activity of teachers in the State of Pará also suffered significant declines, such as the decrease in walking activity when commuting to their workplace, during work and during the week; with respectively 42.9%, 30.6% and 23.4% reduction.